Re-description of the type specimens of Corinnomma hamulatum (Song & Zhu, 1992) stat. rest. (Araneae, Corinnidae) from Hubei, China - Xinxin Li; Chang Chu; Ye-Jie Lin (Biodiversity Data Journal)
Corinnomma Karsch, 1880 comprises 14 species, distributed in Asia, Africa and America. Amongst Asian species, Castianeira hamulata Song & Zhu, 1992 was considered as a junior synonym of Co. severum (Thorell, 1877) by Deeleman-Reinhold (2001).The species Corinnomma hamulatum (Song & Zhu, 1992) stat. rest. is resurrected from its synonymy with C. severum (Thorell, 1877). Photos and morphological re-description of the type specimens are presented. The results of species delimitation using the Poisson Tree Process also support the resurrection of this species.